Problems of the organizational providing of psychological work in divisions of the state traffic Inspectorate - Petrov, V.E.; Kokurin, A.V.; Yurinova, Y.V. (Psihologiâ i pravo, 2016)
The article analyzes the problems of the organizational providing of psychological work in divisions of the state traffic Inspectorate. Detailed the range of tasks that need to be implemented to psychologists, and specifics of the state traffic Inspectorate. The features of carrying out of activities of professional psychological selection of candidates for service, psychological training, prevention and other support activities. Potentially conflicting interaction of inspectors of traffic police with the participants of traffic, the inability to predict traffic situations and the psycho drivers necessitate treatment to psychological knowledge and the application of the constant efforts of specialists-psychologists. It is shown that the replacement of tenured psychologists psychologists state traffic Inspectorate of the territorial body of internal Affairs will not amount to nor the volume of work nor its quality. Psychological work with the personnel of the state traffic Inspectorate should only be carried out by psychologists of this unit. Eventually psychologist in the state traffic Inspectorate has expressed prospects and can not be replaced by the activities of other specialists. Статья посвящена анализу проблем организационно-штатного обеспечения психологической работы в подразделениях Госавтоинспекции. Детализирован круг задач, которые необходимо реализовать психологам, и специфика деятельности Госавтоинспекции. Раскрыты особенности проведения мероприятий по профессиональному психологическому отбору кандидатов на службу, психологической подготовке, профилактике и иным видам обеспечивающей деятельности. Потенциально конфликтное взаимодействие инспекторов Госавтоинспекции с участниками дорожного движения, невозможность прогнозирования дорожных ситуаций и психотипов водителей обусловливают необходимость обращения к психологическому знанию и приложения постоянных усилий специалистов-психологов. Показано, что замена штатных психологов Госавтоинспекции психологами территориального органа внутренних дел не будет равнозначной ни по объему проводимой работы, ни по ее качеству. Психологическая работа с личным составом Госавтоинспекции должна осуществляться только психологами этого подразделения. В конечном счете деятельность психолога в Госавтоинспекции имеет выраженные перспективы и не может быть заменена деятельностью иных специалистов.